High-accuracy tennis players linearly adjust racket impact kinematics according to impact height during a two-handed backhand stroke - Zhang, S.; Sado, N.; Fuji, N. (Sports Biomechanics, 2022)
We hypothesised that high-accuracy players more linearly coordinate racket kinematics with impact heights under random height conditions than low-accuracy players. We compared the adjustments of racket kinematics according to impact height between high- and low-accuracy players. Fourteen male tennis players hit the incoming balls with a two-handed backhand at different impact heights (21-108% of body height) to a target area. The cluster analysis on accuracy divided participants into high- (n = 7, 48.6 ± 2.4%) and low- (n = 7, 32.4 ± 4.8%) accuracy groups. Most of the high-accuracy players linearly decreased the horizontal velocity, increased the vertical velocity, and increased the face angle of racket (R2 = 0.42, 0.36, 0.66) as impact heights increased, while the low-accuracy group only linearly increased face angle (R2 = 0.46) but not linearly adjusted horizontal and vertical velocities (R2 = 0.02, 0.14). The linearities between horizontal velocity and face angle and between vertical velocity and face angle in high-accuracy group (R2 = 0.40, 0.26) were significantly stronger than those in low-accuracy group (R2 = 0.07, 0.08). We found that the high-accuracy players coordinate more racket kinematics and adopt a set of consistent solutions of adjustment according to impact heights. We suggest that players linearly adjust the velocities and the face angles of rackets according to impact heights when prioritising the accuracy.